Improving Early Childhood Literacy through Reading Corner in Kindergarten: Meningkatkan Literasi Anak Usia Dini Melalui Sudut Baca di Taman Kanak-Kanak - Nuraini, Saniah; Maruddani, Raoda Tul Jannah; Anwar, Kaspul; Astria, Rani; Munawaroh, Munawaroh (Universitas Muhammadiyah Sidoarjo, 2023)
General Background: Literacy in early childhood is a fundamental aspect that supports language, cognitive, and social development. Specific Background: However, many kindergarten-aged children face limited stimulation, and reading activities are often less engaging due to lack of supportive media. Knowledge Gap: Previous studies have examined early literacy practices, but few have explored the practical role of reading corners in kindergarten settings. Aims: This study aims to describe the implementation of reading corners and their contribution to improving literacy skills among children aged 5–6 years at TK Negeri 05 Mekarsari. Results: The findings indicate that the reading corner facilitated significant improvements in children’s abilities to recognize letters, increase vocabulary, and retell stories. Novelty: This study highlights the contextual application of reading corners as an effective literacy environment that stimulates children’s motivation and active participation. Implications: The results suggest that reading corners can be optimized as a simple yet impactful strategy in early childhood education, emphasizing the importance of teacher creativity and parental involvement in strengthening literacy culture from an early age. Highlights: Reading corner improves children’s literacy in kindergarten Supports vocabulary growth and storytelling skills Strengthens literacy culture with teacher and parent roles Keywords: Early Childhood Education, Literacy, Reading Corner, Vocabulary, Storytelling